Factors Influencing the Cyberslacking Behavior and Internet Abusive Intention in Academic Settings: A Structural Equation Modeling Approach - Rani Das, Shampa; Hassan Seif, Mohammad; Mahmud, Imran; Vafaei-Zadeh, Ali (International Journal of Psychosocial Rehabilitation, 2020)
In this study, a new research model is proposed to evaluate the abusive intention of cyberslacking behavior among the employees of a company. Cyberslacking can be considered the non-productive behavior where the employees get engaged in personal activities on the internet during office hours, leaving their assigned activities behind. This behavior creates a psychological effect on the employees, and productivity gets diminished as a result. The aims of this study were firstly to find out the factors that influence cyberslacking behavior and secondly to examine whether there exists any relationship between cyberslacking behavior and internet abusive intention. In our model, low self-esteem, private demand, and rules and regulations have a direct impact on cyberslacking behavior, and 4 hypotheses were developed accordingly. Data was collected from 106 academics from two different universities through a survey questionnaire. SPSS v.21 was used to calculate the frequency of the demographic questionnaire, and Smart PLS v.3.0 was employed to test the hypotheses. According to the result, both the self-esteem and private demand had a significant effect, but rules and regulations did not have a significant effect on cyberslacking behavior. Most importantly, our newly proposed model established the relationship between cyber-slacking and abuse intention, and the hypothesis resulted in significance.